ANALYSIS OF DISTRIBUTION OF LAND IN RURAL SETTLEMENTES OF THE SOUTH HALF OF RIO GRANDE DO SUL: THE PERSPECTIVE OF A SUSTAINABILITY COMPATIBLE - Jefferson Marçal da Rocha; Francis Casagranda Zanella; Rafael Cabral Cruz (Redes, 2015)
This article analyzes the process of land distribution and the main production strategies adopted in the rural settlements of the southern half of the Rio Grande do Sul State (RS, Brazil) in recent years, considering the environmental compatibility with the size of the lots. Questionnaires and semi-structured interviews were conducted with qualified agents related to the agrarian region, as well as analysis of documents and bibliographies. The region studied had in their formation process of environmental transformation that constituted the Pampa biome, which is the result of coevolution between humans and biota, since the occupation of the territory by people from Tradition Umbu, who introduced fire management for hunting. With the arrival of Europeans and extensive livestock, the system was transformed through a process of environmental adaptation, resulting in the current form of the biome, with fields of high biodiversity. During the twentieth century this system was strongly influenced by the set of strategies and techniques related to agricultural production and agribusiness expansion in the region, that caused significant losses of biome biodiversity. In the 1980s, from social pressures for land reform in the region, emerged settlement policies with perspective of a strategy to encourage the development of the southern half of the RS. In these allotments, lands were divided into rural modules ranging from 10 to 30 hectares. The results demonstrate that the method used in the distribution, combined with conventional agricultural practices, will not guarantee environmental preservation of biome and will not make possible the reproduction of socioeconomic families in the medium and long term. From this analysis, it is evident that lots distributed, conditioned on socioeconomic and cultural fabric existing in the region, will lead to further loss of biodiversity and social inequalities. This process can only be reversed with consistent distribution methods and practice of compatible agriculture, on the basis of sustainable rural development.